The onset of a pandemic: impact assessments and policy responses in Malaysia during COVID-19 - Khalid, Haniza; Mat Ghani, Gairuzazmi; Sanusi, Zainal Abidin; Mohd Rosli, Zouhair; Wan Mohd Nor, Murni; Syed Hussien, Sh Fatimah Alzahrah; Mohamad Jamil, Siti Nurnadilla; Ahmad, Siti Nuraishah (United Nations Development Programme, 2021)
This report is a call to action, to prepare for future crises, and the ones that we are experiencing today to tackle the multi-faceted social and economic dimensions of crises. It is, above all, a call to focus on people – women, youth, low-wage workers, small and medium enterprises, the informal sector and on vulnerable groups who are already at risk. Rapid assessments during the first months of the pandemic were critical to pinpoint the social, economic and political impacts of the crisis, and discover ways to mitigate them with sustainable, resilient and rights-based solutions forged through both the public and private sector.